'I do it for the kids': understanding the implications of being a volunteer coach in a community youth sport club in New Brunswick, Canada. Issue 3 (3rd July 2022) - Edwards, Jonathon; Kulczycki, Cory
ABSTRACT: Community sport organizations provide youth with opportunities to engage in organized sport through the dedication of volunteers. One group important to the implementation of programs are coaches. Therefore, the purpose of this research was to explore the sacrifices of a volunteer coach at the recreational, competitive, and high-performance level in New Brunswick (NB), Canada. Interviews were the main source of data collection. This research draws on serious leisure literature to gain an understanding of the sacrifices of being a volunteer coach. The findings revealed that volunteer coaches' sacrificial factors included time sacrifice, coach education, travel, hotel and food expenses, and missed opportunities for career earnings. Based on the findings, it is suggested that sacrifices often become inherent volunteering norms that are taken for granted, where there are no other options if the sport organizations want to ensure the programs are administered.